2006
DOI: 10.1097/01.mej.0000228451.15103.89
|View full text |Cite
|
Sign up to set email alerts
|

Emergency outpatient services in the city of Berlin: factors for appropriate use and predictors for hospital admission

Abstract: According to a self-constructed index measuring appropriateness of emergency service use, about half of the patients' visits would have to be classified as inappropriate. Age, chronic illness and the time of day of the emergency service attendance were significantly associated with appropriateness of use. The probability of a hospital admission following the emergency treatment increased with patients' age and the physician's evaluation of treatment urgency. Remarkably, and contrary to the results of internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 21 publications
3
24
1
3
Order By: Relevance
“…Researchers have used varying definitions of urgency and non‐urgency, which makes an appraisal of the present findings difficult. Nonetheless, studies with a similar approach have reported comparable results . For example, our research group previously developed an inappropriateness index for ED or GED utilization that combined both patient and system perspectives, reporting that ethnicity was not a significant predictor for inappropriate use of EDs, analogous to the current findings based on a composite index.…”
Section: Discussionsupporting
confidence: 69%
“…Researchers have used varying definitions of urgency and non‐urgency, which makes an appraisal of the present findings difficult. Nonetheless, studies with a similar approach have reported comparable results . For example, our research group previously developed an inappropriateness index for ED or GED utilization that combined both patient and system perspectives, reporting that ethnicity was not a significant predictor for inappropriate use of EDs, analogous to the current findings based on a composite index.…”
Section: Discussionsupporting
confidence: 69%
“…The interviews were held with those patients -both walking and not walking -who were considered capable of answering, aware of the reality surrounding them [52] and not younger than 15 [1,13]. In the A&ED the interviews were held with all the patients who, regardless of the urgency code they had been attributed, were considered by the nurse in charge of triage as possible non-urgent patients.…”
Section: Methodsmentioning
confidence: 99%
“…Older patients have higher rates of hospital admission, and longer hospital stays than the general population, which accounts for a disproportionate number of hospital bed days [1]. Moreover, there are even higher rates of hospital admissions of older people who live in residential aged care facilities [2].…”
Section: Introductionmentioning
confidence: 99%